2019
DOI: 10.3390/ijerph16245015
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Inequity: Evaluation of an Intervention to Improve Accessibility and Quality of a Green Space

Abstract: Green space areas offer several benefits that support our physical, psychological, and social health. However, the level of engagement with green space areas may not be the same across population groups. Using a mixed-method research design, we investigated the use of a green space area and whether and how the area was beneficial for health, social inclusion, and physical activity for all socioeconomic groups in a suburban area in Norway. The study showed significantly increased use of the area from 2015–2018 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 65 publications
2
21
0
1
Order By: Relevance
“…The role of quality of design for disadvantaged communities was also observed by Anthun et al [41], who evaluated the enhancement of a green cycling and walking path along the coast in a suburban area in Norway, with the aim to improve the accessibility to the city and the quality of green spaces. By using questionnaire surveys, structured interviews, and digital counts), they found that the area residents were overall satisfied with the intervention and used the path, but residents with lower socioeconomic status were the least satisfied with the availability and quality of the new infrastructure, despite reporting high frequency of use.…”
Section: Interventions With a Focused Approachmentioning
confidence: 67%
See 4 more Smart Citations
“…The role of quality of design for disadvantaged communities was also observed by Anthun et al [41], who evaluated the enhancement of a green cycling and walking path along the coast in a suburban area in Norway, with the aim to improve the accessibility to the city and the quality of green spaces. By using questionnaire surveys, structured interviews, and digital counts), they found that the area residents were overall satisfied with the intervention and used the path, but residents with lower socioeconomic status were the least satisfied with the availability and quality of the new infrastructure, despite reporting high frequency of use.…”
Section: Interventions With a Focused Approachmentioning
confidence: 67%
“…No studies were excluded based on study design. A total of 10 papers were included in the final review [36,[40][41][42][43][44][45][46][47][48].…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations